Effect of the mold on the residual strain field monitored with optical fibers sensors in resin transfer molding processes. (September 2014) - Waris, Marc; Liotier, Pierre-Jacques; Drapier, Sylvain
Fiber Bragg gratings provide accurate and non-intrusive strain sensors. They can be embedded into fibrous preforms to deliver real-time information on ongoing processes. The possibility of using the strain-induced birefringence of the fiber Bragg gratings to extract information on the effective strain state of the composite at the end of the process has already been demonstrated. This effect can be used to estimate the residual strain field in composites manufactured by resin transfer molding. The strain fields calculated with the associated optoelastic three-dimensional model are shown to compare well with the strain fields calculated using classical laminated plate theory. The fiber Bragg gratings are then used here in order to study the influence of the nature of the mold on the residual strain field in composite plates and furthermore to infer the kinematic conditions applied by the mold on the part during cooling by using two different molds, an aluminum mold and a HexTool™ composite mold. It is demonstrated by both in situ measurements using fiber Bragg grating in a closed mold under thermomechanical loading and mesoscopical external observations that the thermal expansion of the mold is determinant in the residual strain field development from the onset of the resin curing stage.